2010
DOI: 10.1104/pp.110.162123
|View full text |Cite
|
Sign up to set email alerts
|

The Seed Composition of Arabidopsis Mutants for the Group 3 Sulfate Transporters Indicates a Role in Sulfate Translocation within Developing Seeds      

Abstract: Sulfate is required for the synthesis of sulfur-containing amino acids and numerous other compounds essential for the plant life cycle. The delivery of sulfate to seeds and its translocation between seed tissues is likely to require specific transporters. In Arabidopsis (Arabidopsis thaliana), the group 3 plasmalemma-predicted sulfate transporters (SULTR3) comprise five genes, all expressed in developing seeds, especially in the tissues surrounding the embryo. Here, we show that sulfur supply to seeds is unaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 64 publications
2
48
0
2
Order By: Relevance
“…S9). By analysis of public microarray datasets derived from tissue/cell types samples of embryos (Le et al, 2010;Zuber et al, 2010;Belmonte et al, 2013), we found these five organ-size genes were preferentially expressed at the mature-green, bentcotyledon, and/or the linear-cotyledon stages (Supplemental Fig. S11).…”
Section: Clf Coordinates Key Regulators Within Molecular Modulesmentioning
confidence: 99%
See 2 more Smart Citations
“…S9). By analysis of public microarray datasets derived from tissue/cell types samples of embryos (Le et al, 2010;Zuber et al, 2010;Belmonte et al, 2013), we found these five organ-size genes were preferentially expressed at the mature-green, bentcotyledon, and/or the linear-cotyledon stages (Supplemental Fig. S11).…”
Section: Clf Coordinates Key Regulators Within Molecular Modulesmentioning
confidence: 99%
“…Blue line shows average relative expression levels. F, Relative expression levels of CRGs in 42 embryonic compartments at six stages of seed development (Zuber et al, 2010). Samples were as described in Supplemental Data Set 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An S transporter gene, SULTR3;3, was detected in the QTL interval for N:S ratio on chromosome 20. Group 3 sulfate transporters are predicted to be located on the plasma membrane (Kataoka et al 2004;Zuber et al 2010), and could be involved in sulfate translocation between seed compartments (Zuber et al 2010). Selenate uptake in plants is mediated by sulfate transporters because of chemical similarities between S and Se (Anderson 1993).…”
Section: Putative Candidate Genes In the Vicinity Of Qtl Intervalsmentioning
confidence: 99%
“…A list of all analyzed microarray experiments can be found in Supplemental Data Set 2 online. The complete microarray data set (Seed Total, 101 experiments) was partitioned in different subseries: Germination Total (67 experiments focusing on seed germination, based on different sources), Development Total (34 experiments focusing on seed development, based on the Goldberg-Harada data set; http://seedgenenetwork.net/; Le et al, 2010;Zuber et al, 2010) (also available via GEO, http://www.ncbi.nlm.nih.gov/ geo, accession number GSE12404), and Development Endosperm (24 experiments, a subseries of the Development Total data set focusing only on endosperm-derived data). Based on embryo development, the Arabidopsis endosperm data set contains preglobular, globular, heart, linear cotyledon, and mature green stages.…”
Section: Arabidopsismentioning
confidence: 99%